1989
DOI: 10.1021/j100338a046
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of solvent-sorting effects. 1. A Menschutkin reaction in mixed solvents

Abstract: The second-order rate constant /capp for the reaction between (C2H5)3N and CH3I has been determined at 30.0 °C in cyclohexane and in mixtures of cyclohexane with variable amounts (up to ca. 0.3 M) of the following cosolvents (S); 7V,/V-dimethylacetamide, cyclohexanecarbonitrile, cyclohexyl methyl ketone, butanone, tetrahydrofuran, ethyl acetate, cyclohexyl chloride, methyl cyclohexanecarboxylate, cyclohexyl methyl ether, dibutyl ether, nitrobenzene, 7V,(V-dimethylbenzamide, benzonitrile, acetophenone, benzophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…[9]), which coincides with literature data (14) and is interpreted as due to the hydrogen bond donor ability of the H amino group not involved in the intramolecular hydrogen bond.…”
Section: (B) Studies In Pure Solventssupporting
confidence: 91%
See 1 more Smart Citation
“…[9]), which coincides with literature data (14) and is interpreted as due to the hydrogen bond donor ability of the H amino group not involved in the intramolecular hydrogen bond.…”
Section: (B) Studies In Pure Solventssupporting
confidence: 91%
“…The importance of such phenomena has been recognized not only for spectroscopic studies but also for the interpretation of equilibrium and kinetic data (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider an effective solvent polarity measure, determined as the solvatochromic shift of the Franck–Condon (FC) excitation energy of chromophores. The empirical polarity scale thus defined, such as the Kosower Z factor and E T (30), , gauges the solvating power of solvents, viz., solvent-induced stabilization of dipolar solutes. While this scale correlates well with ε 0 , especially for aprotic dipolar solvents, it yields considerably higher polarity for, e.g., nondipolar but quadrupolar solvents, such as benzene and supercritical carbon dioxide, than their ε 0 values. , This discrepancy arises from electrostatic interactions between the solute dipole and solvent quadrupole moments that are not accounted for in the conventional dielectric constant. Since these interactions play an important role in solvent reorganization, the empirical polarity scale offers a better measure than ε 0 to describe solvation effects in various charge transfer and shift processes in this solvent class. Analogously, due to ion monopole–solute dipole interactions, the solvating power and thus effective polarity of RTILs are substantially higher than the predictions made on the basis of their static dielectric constants. This trend was demonstrated by many earlier experiments and simulations, ,, where solvation stabilization of polar solutes in various RTILs was found to be comparable to and even exceed that in highly dipolar solvents.…”
Section: Resultsmentioning
confidence: 97%
“…In this article, we apply the CQS description to study solvation in binary mixtures of nonpolar and quadrupolar solvents. It has been found that quadrupolar solvents, when mixed with nonpolar solvents 20 of comparable dielectric constants, enhance the effective polarity of the medium considerably even at small concentrations, analogous to the effect produced by dipolar solvents. , One well studied example is kinetics of Menshutkin reactions . When benzene is added as a cosolvent to cyclohexane, the reaction rate between, e.g., triethylamine and iodomethane in the mixture increases rapidly with the mole fraction of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…When benzene is added as a cosolvent to cyclohexane, the reaction rate between, e.g., triethylamine and iodomethane in the mixture increases rapidly with the mole fraction of benzene. Its rate constant in pure benzene is larger than that in pure cyclohexane by nearly 4 orders of magnitude . Another example is the solubility of water, which was found to increase with the benzene concentration in the binary mixture of benzene and cyclohexane …”
Section: Introductionmentioning
confidence: 99%